2019
DOI: 10.1016/j.pmedr.2019.100942
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational effects of witnessing domestic violence: Health of the witnesses and their children

Abstract: Studies that explore intergenerational effects of witnessing domestic violence during childhood (“witnessing”) are lacking. We examined effects of witnessing on general health status for adults who witnessed domestic violence during childhood and their children. Cross-sectional data from population-based phone interviews conducted in Philadelphia during 2012–2013 provided health information for 329 parents and children, and parent's witnessing exposure. We used propensity scores to predict parent's witnessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Even in incidents where physical harm of officers, offenders and witnesses is avoided, deleterious consequences from these tactics can appear. Research suggests that witnessing violent acts or aggressive behavior in policing efforts has long-term, and potentially devastating effects, particularly on children (Forke et al , 2019). Finally, there is concern that these aggressive tactics are disproportionately used against minorities, thus furthering the distrust and anger toward police (ACLU, 2014) in these disempowered groups.…”
Section: Existing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in incidents where physical harm of officers, offenders and witnesses is avoided, deleterious consequences from these tactics can appear. Research suggests that witnessing violent acts or aggressive behavior in policing efforts has long-term, and potentially devastating effects, particularly on children (Forke et al , 2019). Finally, there is concern that these aggressive tactics are disproportionately used against minorities, thus furthering the distrust and anger toward police (ACLU, 2014) in these disempowered groups.…”
Section: Existing Researchmentioning
confidence: 99%
“…It is not just physical risk that increases with the use of these techniques and tools. There are long-term mental health effects for the witnesses of incidents of police militarization, especially on children who may be collateral in the execution of this approach (Forke et al , 2019). Given the aura it creates about the police and the fact that these techniques are deemed to be discriminatory in their application, a decline in public trust may be a result (ACLU, 2014).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Relational violence has a negative outcome on the entire family unit. A study in the United States has shown that witnessing relational violence as a child can cause negative health effects in future generations [23]. Over the course of one year in the Unites States, approximately 20,000 children received residential domestic violence services, and an additional 23,000 adults received advocacy and support [20].…”
Section: Impact On Children and Familiesmentioning
confidence: 99%
“…Violence or abuse is intense negative stress (70). Moreover, cumulating evidence showed that abused parents are at increased risk for perpetuating maladaptive parenting practices, which would be transmitted to generations to come through not just intimate (71,72), but also the underlying uncontrollable epigenetic mechanisms (73).…”
Section: Violence and Abusementioning
confidence: 99%